2016
DOI: 10.1080/03639045.2016.1185436
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the wettability of excipients by surfactant and its impacts on the disintegration and release of tablets

Abstract: The modulation of the wetting of pharmaceutical excipients by surfactant had changed the disintegration time of tablets and drug release rate to a greater extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The findings were consistent with a matrix tablet containing poly(maleic acid-alt-octadecene) potassium salts (PAM-18K), which was reported in the study to reduce the drug release rate when the hydrophobic polymer was added [ 21 ]. The wettability of surfactant excipients, as well as their effects on the disintegration and release of plain tablets, was investigated [ 38 ]. The results showed that the wetting ability by adding surfactants to the formulation affects the disintegration and release of the tablets.…”
Section: Resultsmentioning
confidence: 99%
“…The findings were consistent with a matrix tablet containing poly(maleic acid-alt-octadecene) potassium salts (PAM-18K), which was reported in the study to reduce the drug release rate when the hydrophobic polymer was added [ 21 ]. The wettability of surfactant excipients, as well as their effects on the disintegration and release of plain tablets, was investigated [ 38 ]. The results showed that the wetting ability by adding surfactants to the formulation affects the disintegration and release of the tablets.…”
Section: Resultsmentioning
confidence: 99%
“…Several research groups have developed new approaches to quantify the fundamental disintegration mechanisms using high-speed imaging (Berardi et al, 2018;Basaleh et al, 2020), terahertz pulsed imaging (Markl et al, 2018Al-Sharabi et al, 2020), magnetic resonance imaging (Quodbach et al, 2014a,b;Dvořák et al, 2020;Catellani et al, 1989), and water uptake and (swelling) force measurements (Caramella et al, 1986;Peppas and Colombo, 1989;Tomas et al, 2018). The liquid uptake and wettability of powder and pharmaceutical compacts were also investigated using the sessile drop method, where several groups observed a correlation between the wettability characteristics and the disintegration/dissolution performance of tablets for a range of different formulations (Yang et al, 2016(Yang et al, , 2018Liu et al, 2018;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The PBS solution containing SDS (0.5 wt%) was used as the in vitro release medium. The addition of SDS was to increase the solubility of hydrophobic SIM, which was conducive to its release in the medium [ 33 ]. Two kinds of the SIM-loaded NFMs (NO.1 and NO.2) were cut into circular specimens with a diameter of 15 mm.…”
Section: Methodsmentioning
confidence: 99%